VERIFICATION OF ANALYTICAL METHOD FOR DETERMINATION OF AZIDOMETHYL BIPHENYL TETRAZOLE (AZBT) AS IMPURITY IN CANDESARTAN CILEXETIL TABLETS - Maharani Budiyarso, Rahmaditha
Azidomethyl Biphenyl Tetrazole (AZBT) is an azide compound classified as a contaminant in the raw material of Candesartan Cilexetil (CC) and is predicted to be carcinogenic and mutagenic based on in silico studies. Therefore, a method is required to determine the presence of AZBT in both the raw material and pharmaceutical formulations. The aim of this study was to obtain a method for determination of AZBT in Candesartan Cilexetil tablets by adjusting and/or modifying the methods described in USP NF35. The method is based on High-Performance Liquid Chromatography (HPLC) analysis with a UV-Visible detector at a wavelength of 254 nm and a photodiode array (PDA) detector in the wavelength range of 200 - 380 nm. The XBridge L1, 4.6 x 150 mm; 5 µm (XBridge Column C18) column was used as a reversed-phase with a mobile phase consisting of a mixture of acetonitrile, water, and a 0.1% trifluoroacetic acid solution, with a gradient elution at a flow rate of 1 mL/min. The method verification parameters and acceptance criteria are based on the ICH Q2 guidelines, including specificity, linearity, limit of detection, limit of quantification, accuracy, precision, and range. The verification results showed a column capacity factor (k') of 3.49, a selectivity factor (?) of AZBT with respect to the Candesartan RC G and RC A peaks of 1.82 and 1.68, and a resolution factor (Rs) of AZBT with respect to Candesartan RC G and RC A of 9.2 and 14.4. The AZBT stock solution in the range of 0.10 - 0.35 µg/mL, equivalent to 40 - 140% of the AZBT working concentration (0.25 µg/mL), provided a linear calibration curve with the equation of Y = 22.98x + 0.022 and value of 0.9994. The statistically calculated limit of detection (LOD) and limit of quantification (LOQ) were 0.01 and 0.03 µg/mL, respectively, while those of Signal-to-Noise (S/N) ratio-based were 0.03 and 0.08 µg/mL, respectively. The method accuracy, expressed as percent of recovery, is 103.6%, while the precision, expressed as the relative standard deviation (RSD) for the system suitability and intermediate precision tests, was in the range of 2.2 to 2.6%. Overall, the obtained results fulfill the specified acceptance criteria, indicating that the developed method can be used for the determination of AZBT contaminant in Candesartan Cilexetil tablets. Analysis of actual Candesartan Cilexetil (CC) tablets commercially available, showed that AZBT was not detected.